Pengaruh Metode Latihan Interval dan Pyramid dengan Pola Latihan Resistance Band Ladder Drills Terhadap Peningkatan Power Endurance pada Pemain Futsal Putri UPI - Rahayu, Iis Sri; Sidik, Dikdik Zafar (Jurnal Kepelatihan Olahraga, 2021)
This study aims to determine the difference in the effect of interval and pyramid training methods with Resistance Band Ladder Drills training patterns on increasing power endurance in UPI Women's Futsal Players. This research is an experimental research.The population uses active members of UKM upsal Putri SMEs with a research sample using purposive sampling technique wih is divided into two groups, namely the Interval training method and Pyramid training method. The research instrument is Multi Stage Hurdle Jump. Data analysis technique used for normality test, F-test, and T-test by using the help of SPSS software. The results showed a significant increase in the interval training method and the pyramid training meyhod. The conclusion from this study is that the interval training method results are more improved compared to the pyramid.